POSTOPERATIVE INTENSIVE CARE IN PREGNANT WOMEN WITH VARICOSE DISEASE USING MEDICATIONS CONTAINING DIOSMIN (Лучшие интеллектуальные исследования, 2025)
Abstract : Chronic venous diseases of the lower extremities are widespread health issues affecting a significant portion of the population. Pregnancy is a major factor contributing to venous insufficiency in women due to the mechanical pressure exerted by the growing uterus and the hormonal changes induced by the placenta, which affect the vessel walls.